Spatial Development of Construction: Modeling and its Financial and Investment Support - Komelina, Ðžlha; Vasiuta, Viktoria; Miniailenko, Inna (International Journal of Engineering and Technology, 2018)
The modern globalization economy requires new approaches to optimizing the spatial format of regional economies. The international experience in developing spatial development strategies of European countries, the USA, China has been researched in this survey. The key components of spatial development, which are based on the economic, social and ecological components of the region's development, are determined in this article. The analysis of literary sources confirmed the significant role of the construction industry in shaping the spatial economy of the state and its regions. The main type of economic activity of the Poltava region economy is construction, the development of which affects other types of economic activities: mining and processing industry, agriculture, transport, etc. The forecast of the construction contribution to the gross regional product of the Poltava region enabled to identify problems and prospects for the construction development. The authors have used the production function in order to model the dependence of the Poltava regionâ€™s key indicator - the gross regional product from the contribution of each type of economic activity, taking into account the available potential and their investment support. The calculations allowed to determine the growth points of the gross regional product and to construct a model that takes into account the contribution of extractive industry, construction and transport to the development of the region. As a result of redistribution of investment support of the studied industries, the optimal gross regional product was obtained. On the basis of the conducted modeling, a mechanism for regulating financial and investment support for spatial development of construction was developed.Â